1970
DOI: 10.3126/njst.v10i0.2822
|View full text |Cite
|
Sign up to set email alerts
|

Infestation of Rice Root-Knot Nematode in Rice Nurseries in Chitwan

Abstract: A survey was conducted during June-July 2006 in Chitwan to find out the natural infestation of rice root-knot nematode (Meloidogyne graminicola Golden & Brichfield) in rice nurseries. Thirty nurseries were surveyed and 100 seedlings from each nursery were evaluated. Field survey revealed that M. graminicola was widely distributed in most rice growing areas of Chitwan District. Rice root-knot disease was more prevalent in dry bed condition than wet bed. Most of the farmers grew seedlings in upland (dry) soil an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

1970
1970
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…We suggest that this difference in pathogen population density (J2 and eggs) per root unit can be explained, inter alia, by the greater ability of the infective J2 (a) to migrate in a sandy loam soil than in a clay loam soil (Rao & Israel 1972) and (b) to penetrate and infect rice roots under the more dry upland conditions than under the more wet (intermittently flooded) lowland conditions (Bridge & Page 1982;Dangal et al 2009). Also, the thick root diameter, usually observed in upland rice varieties, may also provide a more favourable environment for the multiplication of M. graminicola once inside the roots compared with that observed in lowland rice varieties (Kondo et al 2000;Henry et al 2012;Cabasan et al 2013).…”
Section: Discussionmentioning
confidence: 98%
“…We suggest that this difference in pathogen population density (J2 and eggs) per root unit can be explained, inter alia, by the greater ability of the infective J2 (a) to migrate in a sandy loam soil than in a clay loam soil (Rao & Israel 1972) and (b) to penetrate and infect rice roots under the more dry upland conditions than under the more wet (intermittently flooded) lowland conditions (Bridge & Page 1982;Dangal et al 2009). Also, the thick root diameter, usually observed in upland rice varieties, may also provide a more favourable environment for the multiplication of M. graminicola once inside the roots compared with that observed in lowland rice varieties (Kondo et al 2000;Henry et al 2012;Cabasan et al 2013).…”
Section: Discussionmentioning
confidence: 98%
“…These declining yields are associated with nutrient deficiencies (Kreye et al ., ; Nie et al ., ), as well as biotic factors, in which root‐affecting Pythium spp. ( Pythium graminicola and Pythium arrhenomanes ) and root‐knot nematodes (RKNs), such as Meloidogyne graminicola , are the predominant species (Bridge et al ., ; Dangal et al ., ; De Waele and Elsen, ; Soriano et al ., ; Tandingan et al ., ; Van Buyten et al ., ). In the case of RKNs, infective second‐stage juveniles (J2) penetrate the roots and migrate intercellularly towards the root apex, where they make a U‐turn and move upwards in the vascular bundles to the differentiation zone, where they settle and initiate permanent feeding sites called giant cells.…”
Section: Introductionmentioning
confidence: 99%
“…Lower RKI in simulated lowland was mainly due to reduced penetration of rice roots by M. graminicola in flooded soils (Bridge & Page 1982). Dangal et al (2009) also found higher RKI but lower RLI in upland nurseries than lowland. Similarly, Prot and Matias (1995) found greater root gall indices in upland than in irrigated conditions.…”
Section: Resultsmentioning
confidence: 84%
“…The number of J2 recovered from soil and roots were significantly lower in wet bed, healthy seedbed, lowland and healthy transplanted soil than the in dry bed, M. graminicola infested seedbed, upland transplanted condition and the nematode infested soil respectively (Table 1). Similarly, Dangal et al (2009) found lower J2 population in roots and soil from nurseries in wet bed and lowland than in dry bed and upland, respectively. Soriano et al (2000) Bridge and Page (1982).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation